2019
DOI: 10.1200/jco.2019.37.15_suppl.e14614
|View full text |Cite
|
Sign up to set email alerts
|

Analytical validation of the Oncomine Pan-Cancer Cell-Free Assay in a CLIA- and CAP-regulated laboratory for detection of solid tumor-derived variants in blood plasma.

Abstract: e14614 Background: Assessing tumor-derived somatic variants from blood plasma provides minimally invasive tumor profiling, decreased cost relative to traditional tissue biopsy and rapid turn-around-time. We describe here the analytical validation of the Oncomine Pan-Cancer Cell-Free assay in a CAP-accredited, CLIA-certified laboratory. The assay is designed to detect somatic DNA single-nucleotide variants (SNV), insertions/deletions (INDEL), copy number variants (CNV), and gene fusions in cell-free total nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The previous study using the Oncomine Lung Cell-Free DNA Assay, the same platform with the different assay, demonstrated a sensitivity of 81% with <20 ng of cfDNA at a VAF of 0.1%, whereas our data showed a sensitivity of 50% under the same condition [21]. In the report by the manufacturer, the same assay in the present study showed a sensitivity of 80% at a VAF of 0.1% for SNV [22]. In the present study, most of the analytical performance tests were conducted using reference materials and clinical samples containing only EGFR mutations.…”
Section: Discussionsupporting
confidence: 50%
“…The previous study using the Oncomine Lung Cell-Free DNA Assay, the same platform with the different assay, demonstrated a sensitivity of 81% with <20 ng of cfDNA at a VAF of 0.1%, whereas our data showed a sensitivity of 50% under the same condition [21]. In the report by the manufacturer, the same assay in the present study showed a sensitivity of 80% at a VAF of 0.1% for SNV [22]. In the present study, most of the analytical performance tests were conducted using reference materials and clinical samples containing only EGFR mutations.…”
Section: Discussionsupporting
confidence: 50%
“…In turn, this enables interrogation of limiting amounts of ctDNA (as in low tumor burden samples), and enriches the density of informative sequencing reads which are on-target. Analytical sensitivities of amplicon-based methods are reportedly superior [25,26] compared to hybrid capture-based methods [15,24] for single nucleotide variants (SNVs) and insertion/deletion events (INDELs), in the biologically relevant sub-1% ctDNA range. While multiple analytical and post-analytical factors differ between individual methods, including variant calling algorithms, better sensitivity can at least be partially attributed to the superior on-target capture rate of amplicon-based enrichment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Somatic alterations were identified in tumor tissues by either hybrid capture-based targeted DNA sequencing in using FoundationOne CDx (15) or PCR-amplicon-based target capture using Oncomine (16). Somatic alterations in cell-free DNA (cfDNA) were detected by Oncomine (17) and Guardant360 (18). Lollipop figures were created using the visualize data feature by cBioPortal (19,20) and annotation of the biologic and oncogenic effects and prognostic and predictive significance of somatic molecular alterations were extracted from the OncoKB knowledge base (21).…”
Section: Somatic Alteration Identification and Annotationmentioning
confidence: 99%